ANALYSIS OF CAREER DEVELOPMENT AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH WORK ENGAGEMENT AS AN INTERVENING VARIABLE IN THE OFFICE MEDAN BELAWAN DISTRICT - Arif Budiman; Mesra B; Elfitra Desy Surya (RADJA PUBLIKA, 2024)
This study aims to analyze the influence of career development and compensation on employee performance with work engagement as an intervening variable at the Medan Belawan District Office. This study uses a quantitative approach with a survey method by distributing 51 questionnaires to employees as respondents. Purposive sampling technique is used to determine the sample so that the data obtained is relevant to the research objectives. Data were analyzed using path analysis techniques to measure the direct and indirect effects between variables. The results of the study indicate that career development has a positive and significant effect on employee work engagement and performance. Compensation has a positive but insignificant effect on employee performance but has a positive and significant effect on work engagement. Work engagement also has a positive and significant effect on employee performance. Thus, work engagement acts as an intervening variable that mediates the influence of career development and compensation on employee performance. The results of this study are expected to be input for management in improving employee performance through targeted career development planning, providing fair compensation, and increasing employee work engagement.